Modification of a fluorine–silicone acrylic resin with a free‐radical‐catching agent. Issue 25 (8th March 2018) - Lei, Huibin; He, Deliang; Guo, Yanni; Tang, Yining; Lu, Yao
ABSTRACT: Several kinds of free‐radical‐catching fluorine–silicone acrylic resins with different contents of 2, 2, 6, 6‐tetramethyl‐4‐piperidyl methacrylate (TMPM) were synthesized by solution copolymerization. The chemical structures and properties of the resins were characterized and followed the performances of their respective coatings. The results demonstrate that these kinds of resins showed a high ability to produce nitroxide. The coatings had good thermal stability and hydrophobicity with water contact angles over 100°. Moreover, the weather resistance showed a great improvement for the synergetic protection by bonded TMPM, organic fluorine, and silicone. By aging tests, the modified coatings still maintained excellent mechanical properties with an impact strength and flexibility of 400 N cm and 2 mm, respectively. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46385. Abstract :